Subsurface Imaging of Past Shorelines of Lake Michigan at Manistique, Michigan - Hynek, Madeline R.; Seamans, Jackelyn M; Kleinschmidt, Alexander S.; Jol, Harry M. (My University, 2018)
Lake Michigan has experienced water level fluctuations since its formation 14,000 years ago. These fluctuations have formed a set of visible sand ridges parallel with the current Lake Michigan shoreline and can be seen along the Manistique Embayment located in Michigan’s Upper Peninsula. The most prominent water level fluctuation occurred during the mid- Holocene period when the lake level was at its highest (~4 meters) and is known as the Nipissing phase. The purpose of this research is to determine how the Nipissing high affected the shoreline of Lake Michigan. Using ground penetrating radar (GPR), a noninvasive geophysical technique used to image the subsurface, a 1,100-meter-long transect of the embayment was collected. The GPR system used was a pulseEKKO 1000 with antennae frequency of 100 MHz. Data was collected using a step size of 0.25m and an antennae separation of 1m. Using a Topcon laser level, the topography of the GPR line was collected. The raw data was processed using Sensor and Software’s EKKOproject. The results of the GPR transect show evidence of coastal processes including progradation and aggradation associated with beach ridge formation and will contribute to refining the present paleohydrograph of Lake Michigan.
Color poster with text, charts, graphs, maps and images.
Keywords: Ground penetrating radar; Upper Peninsula (Mich.); Posters